Usability assessment of library related web sites : - Campbell, Nicole (LITA, a division of the American Library Association, 2001)
This book inclubes: chapter 1 defines the concept of usability and provides a synopsis of methods for measuring usability. Chapter 2 discusses some of the important elements to consider when conducting a usability study.